Biological and molecular properties of yellow venom of the Amazonian coral snake Micrurus surinamensis - Fabiana da Rocha Oliveira; Maria das Dores Nogueira Noronha; Jorge Luis Lopez Lozano (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: The coral snake Micrurus surinamensis, which is widely distributed throughout Amazonia, has a neurotoxic venom. It is important to characterize the biological and molecular properties of this venom in order to develop effective antitoxins. METHODS: Toxins from the venom of M. surinamensis were analyzed by two-dimensional polyacrylamide gel electrophoresis and their neurotoxic effects in vivo were evaluated. RESULTS AND CONCLUSIONS: Most proteins in the venom had masses < 14kDa, low phospholipase A2 activity, and no proteolytic activity. The toxins inhibited the coagulation cascade. The venom had neurotoxic effects in mice, with a median lethal dose upon intravenous administration of 700 µg/kg. Immunogenic studies revealed abundant cross-reactivity of antielapidic serum with 14kDa toxins and limited cross-reactivity with toxins < 10kDa. These results indicate that antielapidic serum against M. surinamensis venom has weak potency (0.35mg/ml) in mice.